Report of Participation of PHEA in 21st IFHE World Congress, in Lucerne, Switzerland - Hakeem, Rubina (Nurture, 2008)
IFHE is an International Non Governmental Organization (INGO), hav ing consultative status with the United Nations (ECOSOC, FAO, UNESCO, and UNICEF) and with the Council of Europe. The International Federation for Home Economics (IFHE) serves as a platform for international exchange within the fields of: Family, Home Economics, Food and Nutrition, Health, Consumer Issues and Education. The ultimate goal of the Federation is the improvement in the quality of everyday life for individuals, families and households through the management of their resources.